2009
DOI: 10.1161/atvbaha.109.185546
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Telomerase Reverse Transcriptase Binds to and Protects Mitochondrial DNA and Function From Damage

Abstract: Objective-The enzyme telomerase and its catalytic subunit the telomerase reverse transcriptase (TERT) are important for maintenance of telomere length in the nucleus. Recent studies provided evidence for a mitochondrial localization of TERT. Therefore, we investigated the exact localization of TERT within the mitochondria and its function. Methods and Results-Here, we demonstrate that TERT is localized in the matrix of the mitochondria. TERT binds to mitochondrial DNA at the coding regions for ND1 and ND2. Bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
342
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 320 publications
(377 citation statements)
references
References 35 publications
30
342
1
4
Order By: Relevance
“…Additional studies demonstrated the ability of TERT to antagonize apoptosis induced by topoisomerase inhibitors in PC12 cell line or by oxidative stress in lymphocytes CD4+ model (Lu et al, 2001;Luiten et al, 2003). Such results illustrating the protective role of TERT against ROS were confirmed later in other models (Ahmed et al, 2008;Haendeler et al, 2009;Indran et al, 2011). Although most of these early investigations did not explore the involvement of the reverse transcriptase activity of TERT in this anti-apoptotic mechanism, these results had already outlined a potential function of TERT unrelated to its enzymatic activity and ability to lengthen telomeres (Sung et al, 2005).…”
Section: Relationships Between Tert and Apoptotic Pathwaysmentioning
confidence: 65%
See 3 more Smart Citations
“…Additional studies demonstrated the ability of TERT to antagonize apoptosis induced by topoisomerase inhibitors in PC12 cell line or by oxidative stress in lymphocytes CD4+ model (Lu et al, 2001;Luiten et al, 2003). Such results illustrating the protective role of TERT against ROS were confirmed later in other models (Ahmed et al, 2008;Haendeler et al, 2009;Indran et al, 2011). Although most of these early investigations did not explore the involvement of the reverse transcriptase activity of TERT in this anti-apoptotic mechanism, these results had already outlined a potential function of TERT unrelated to its enzymatic activity and ability to lengthen telomeres (Sung et al, 2005).…”
Section: Relationships Between Tert and Apoptotic Pathwaysmentioning
confidence: 65%
“…Following this hypothesis it was then demonstrated that telomerase, or more specifically the catalytic subunit TERT is able to translocate from the nucleus to the mitochondria following drug treatments or increase of oxidative stress (Ahmed et al, 2008;Haendeler et al, 2009;Santos et al, 2006;Saretzki, 2009) (Figure 2). This new interesting finding was linked to the discovery of mitochondrial targeting sequence at the N-terminal extremity of TERT (Santos et al, 2004).…”
Section: Tert Oxidative Stress and Mitochondriamentioning
confidence: 96%
See 2 more Smart Citations
“…http://dx.doi.org/10.1101/000679 doi: bioRxiv preprint first posted online Nov. 18, 2013; against oxidative stress-induced damage (Haendeler et al 2009). Proteomic analysis of C2C12 cells indicates that respiratory chain proteins are up-regulated by 10 days postdifferentiation (Kislinger et al 2005), resulting in increased potential for generation of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%